Evaluation of Malaria Surveillance System in the Khagrachari District of Bangladesh: An Observational Study (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: A Malaria surveillance system is essential to achieve "Malaria-free Bangladesh" by 2030. Though the system encountered challenges, including poor data quality, this study evaluated it in Khagrachari and rated its main attributes.Materials and methods: An observational study was conducted consisting of survey, secondary data analysis, record review and mixed methods of data collection. The surveillance system was examined using the "2001 United States Centers for Disease Control's updated guidelines for  Evaluating Public Health Surveillance Systems". A total of  1407 patients' data was collected from previous records (2018-2022). Purposively chosen, 22 stakeholders participated in the study, and 128 case investigation forms were assessed.Results: 15(68.18%) out of 22 respondents had 12-year experience on surveillance and 17(77.27%) had formal training. 19(86.36%) respondents reported case definitions were easy-to-use, and 14(63.64%) participants claimed data tools could accommodate changes. 731(51.95%) cases were detected through Passive Case Detection (PCD) and nearly one-fourth (26.15%) cases by Government Organizations. The results of 'Timeliness' against the number of cases investigated within day one was 64.84%. Trends of cases showed significant decline ( 2 trend = 683.03, p = 0.0001).Conclusion: The system is effective as it meets most of its  objectives.JCMCTA 2025 ; 36 (2) : 99-106